Effects of Student Self-Assessment and Using GeoGebra™ on Students’ Achievements and Self-Directed Learning in Mathematics Lessons in a Junior High Classroom - Phoodee, Wuttichai (SEAMEO Regional Centre for QITEP in Mathematics, 2023)
This paper demonstrates a teacher-as-researcher intervention study of Student Self-Assessment, utilizing GeoGebra activities on the topic of relationships of geometric figures. The teacher researcher studied students’ achievements and self-directed learning by including Student Self-Assessment (SSA) and by teaching procedural knowledge and conceptual knowledge using eleven GeoGebra-based tasks at the same time. The data were collected via questionnaire, interview, as well as two tests which were given after task 6 and task 11 were completed. The teacher researcher oversaw the progress of the 24 Thai male and female junior high mathematics students (13-14 years old), and offered prompt guidance and support using normal classroom techniques.The findings indicated that the utilization of SSA and GeoGebra had a positive impact on these students' academic performance and their ability to take charge of their learning in mathematics classes. Specifically, the intervention led to 1) improved communication between student and teacher; 2) improved students’ understanding of what they needed to learn; 3) improved students’ confidence to ask for help from the teacher; 4) promoted student achievement; and 5) promoted self-directed learning in mathematics lessons.